A note on the effect of the fiber curvature on the micromechanical behavior of natural fiber reinforced thermoplastic composites - M. A. Escalante-Solis; A. Valadez-Gonzalez; P. J. Herrera-Franco (eXPRESS Polymer Letters)
To better understand the role of the fiber curvature on the tensile properties of short-natural-fiber reinforced composites, a photoelastic model and a finite element analysis were performed in a well characterized henequen fiber-high density polyethylene composite material. It was hypothesized that the angle of orientation of the inclusion and the principal material orientation with respect to the applied load was very important in the reinforcement mechanics. From the photoelastic and finite element analysis it was found that the stress distribution around the fiber inclusion was different on the concave side from that observed on the convex side and an efficient length of stress transfer was estimated to be approximately equal to one third the average fiber length. This approach was used to predict the short-natural-fiber reinforced composite mechanical properties using probabilistic functions modifications of the rule of mixtures models developed by Fukuda-Chow and the Fukuda-Kawata. Recognizing the inherent flexibility that curves the natural fibers during processing, the consideration of a length of one third of the average length l should improve the accuracy of the calculations of the mechanical properties using theoretical models.